COVID-19 Vaccination among minority Cancer Patients: Recommendation of the International Geriatric Radiotherapy group - Nguyen, Nam P; Oboite, Eromosele; Oboite, Joan; Mazibuko, Thandeka; Vuong, Te; Baumert, Brigitta G.; Lehrman, David; Gonzalez, Alejandro Chagoya; Loganadane, Gokoulakrichenane; Dutta, Suresh; Motta, Micaela (Archives of Clinical and Biomedical Research, 2021)
Abstract not available in the source database.